2017
DOI: 10.1002/er.3776
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and assessment of a thermochemical energy storage using salt hydrates

Abstract: Summary Several research studies have revealed the potential use of salt hydrates in thermal energy storage applications. These materials dissociate into anhydrous salts and release water vapor when subjected to heat source. The latter salt has the capability to store the energy that was supplied for dehydration upon heating. This thermal energy can be extracted by flowing cooler water or water vapor through the salt to obtain sensible heat that can be exploited for several applications, such as heating reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Copper sulphate (CuSO 4 ) (H302, H315, H319, H410) is not one of the hydrates frequently found in the specialized literature, even though its thermodynamic properties are of interest for application at low temperatures 48 , 49 . Copper sulphate CAS-Nr.…”
Section: Methodsmentioning
confidence: 99%
“…Copper sulphate (CuSO 4 ) (H302, H315, H319, H410) is not one of the hydrates frequently found in the specialized literature, even though its thermodynamic properties are of interest for application at low temperatures 48 , 49 . Copper sulphate CAS-Nr.…”
Section: Methodsmentioning
confidence: 99%
“…Several research studies have shown the suitability of salt hydrates for thermal energy storage [45]. These materials dissociate into anhydrous salts, release water vapor when subjected to heat source, and store energy supplied for dehydration upon heating.…”
Section: Inorganic Pcmsmentioning
confidence: 99%
“…The authors concluded that the copper sulfate system could be driven by solar energy or other low temperature renewable energy heat source (55-85 °C), allowing the activation energy of 25.053 kJ/ mol. The salt dehydration studies were mostly in the '60s and '80s (Borchardt and Daniels, 1957;Reisman and Karlak, 1958;Wendlandt, 1962;Mu and Perlmutter, 1981;Sørensen, 1981), and some comparative studies with other thermochemical materials have been published in the last years (Glasser, 2014), (Savchenko et al, 2006), (Al-Abbasi et al, 2017). Wendlandt (1962) studied the dehydration of copper sulfate, concluding that the dehydration from hepta to the trihydrate occurs in two steps and an intermediate phase CuSO 4 •4 H 2 O at high pressures.…”
Section: Copper Sulfatementioning
confidence: 99%